O ritmo da mistura e o compasso da história: o modernismo musical nas Bachianas brasileiras de Heitor Villa-Lobos - Loque Arcanjo Junior (2007)
This work consists of an analysis of Heitor Villa-Lobos` Bachianas Brasileiras in a historical perspective. Composed amongst the years of 1930 and 1945, these masterpieces appeared in Villa-Lobos´ speech as compositions that, since his childhood, would already be in the predestined mind of the musician, as the fruit of his premature intuition. While an autobiographical reading, such interpretation is naturalized in many biographical and musicological works about the author. From a theoretical analysis of the Brazilian Modernism, indicated by experts of the theme, this approach the composer make of his own work pointed to some remarkable features of the Brazilian nationalist modernism, as much in what refers to the search of the essence of the nationality as with respect to the idea of vanguard as one of the elements of modernism in general. After the research, it became obvious, in this context of creation of the works, that the appropriation of Bachs music took a meaning that quite expressed the nationalist ideas of musical modernism, trampled on the construction of the national unity. The Bachs music, from its appropriation by the nineteenth century musical romanticism, turned to symbol of nationalism and development and, in this way, later, in Brazil, was swallowed by Villa-Lobos anthropophagical reading. From the appropriation of the Brazilian primitive musicality, mingled with the elements of Bachs music, it could be verified that the musician constructed with the Bachianas Brasileiras a musical synthesis which, in a context of nation unification, made dialogue distinct and different musical elements. In the rhythm of this mixture, the reading of Mário de Andrades work and the presence of a musicality result of his contact with the popular music, dictated, as far as possible, Villa-Lobos musical writing. In this way, the Bachianas Brasileiras make echo all this diversity, composing a web of meanings which made of Villa-Lobos an expression of the Brazilian culture.